Phenotypic and Haplotype Diversity among Tetraploid and Hexaploid Wheat Accessions with Potentially Novel Insect Resistance Genes for Wheat Stem Sawfly. Issue 1 (1st March 2017) - Cook, J. P.; Blake, N. K.; Heo, H. Y.; Martin, J. M.; Weaver, D. K.; Talbert, L. E.
Abstract : Genetic diversity in breeding programs can be impaired by fixation of alleles derived from a limited number of founder lines. This is demonstrated with the use of a solid‐stem trait derived from the Portuguese landrace 'S‐615' over 70 yrs ago that is widely used to resist the wheat stem sawfly ( Cephus cinctus Norton, WSS) in North America. The objective of this study was to evaluate haplotype diversity underlying the Qss.msub.3BL quantitative trait locus (QTL) that controls the majority of the S‐615 derived solid‐stem genetic variation using single‐nucleotide polymorphism (SNP) assays in a diverse set of 228 solid‐stem tetraploid and hexaploid wheat accessions originating from areas of the world infested with various species of WSS. Haplotype analysis showed all WSS‐resistant hexaploid wheat varieties in North America, except 'Conan', evaluated in this study contain a haplotype associated with the S‐615 solid‐stem allele. In total, 26 haplotypes were identified among the hexaploid and tetraploid accessions at Qss.msub‐3BL . Prevalence of most haplotypes were skewed toward either the hexaploid or tetraploid wheat accessions. The haplotype found in the S‐615‐ hexaploid wheat landrace was not found in the solid‐stem tetraploid landrace accessions evaluated in this study. Haplotype analysis revealed several new haplotypes that have potential to contain novel alleles for solid‐stems at Qss.msub.3BL, which may form the basis for introducing genetic diversity into breeding programs aimed at WSS resistance.